A pintura na literatura: linguagem plástica em Não entres tão depressa nessa noite escura, de António Lobo Antunes - Souza, Aline Prúcoli de (2016)
Based on the book-poem Não entres tão depressa nessa noite escura (Don’t enter that dark night so fast), by the Portuguese write António Lobo Antunes, the correlation between literature and painting is analyzed, aiming at understanding how the plasticity of his language manifests itself when comparing the book to a painting. Departing from four basic elements in a pictorial composition – frame, lines, colour and surface –, we have performed a homological and analogical analysis of António’s textual weaving. It was of great interest to us to understand the new meaning possibilities which the fusion between both arts may offer and add some contribute to the critical discussions around the topic, bearing in mind Lobo Antunes’ narrative. Therefore, it was necessary to revisit the first lines of thought about interart relationship, as well as understanding its current configurations. Our analysis is based on the theoretical writings of thinkers who work (on) the frontier between both languages, such as Anne-Marie Christin, Julio Plaza, Márcia Arbex and George Didi-Huberman. We aim at clarifying the fact that more than reading a text or looking at an image, we can look at a text to learn how to read its structure, as we can read an image when we look at its architecture. The homological and analogical exercise proposed based on a structural and functional approximation of two artistic universes called our attention to the existence of important aspects, which are beyond what a narrative may present in its theme. This way, it was offered to us a new key to read not only António’s text, but literature in general. The research has shown, at last, that (re)integration of two artistic areas makes it possible not only to semantically enrich artistic objects, but also and foremost to intensify the interpretive capacity of those who receive them aesthetically.